Integrating Diamond-Like Carbon into Nanostructure Designs (Fabricating Microscale and Nanoscale Architectures of Diamond-Like Carbon Films) - Li, X. (2014)
Ceramic Integration and Joining Technologies: From Macro to Nanoscale